PENGARUH MEDIA VIDEO TUTORIAL TERHADAP HASIL BELAJAR MENGGAMBAR ILUSTRASI SISWA KELAS XI IPA DI SMA NEGERI 1 BATANG KAPAS PESISIR SELATAN - UUTIYA DARLIVIE; Yusron Wikarya (Universitas Negeri Padang, 2021)
This study aims to determine whether there is a significant difference between student learning outcomes taught using video tutorial media and student learning outcomes being taught without using video tutorial media in learning cultural arts at SMA Negeri 1 Batang Kapas Pesisir Selatan. This type of research is a quantitative study with a quasi-experimental form. The instrument used was a drawing test which was carried out by pretest and posttest. The results showed that the average value of learning outcomes to draw illustrations in the experimental class using video tutorial media was higher than the control class who did not use video tutorial media. Based on hypothesis testing using SPSS version 16.0, the value of tcount = 2.663 and ttable = 1.308 with a significant level (α = 0.05) indicates that there is a significant difference between the two classes.Keywords: Learning Media, Video Tutorials, Learning Outcomes, Fine Arts.